Targeting Theranostics of Atherosclerosis by Dual‐Responsive Nanoplatform via Photoacoustic Imaging and Three‐In‐One Integrated Lipid Management. Issue 5 (20th December 2022) - Ma, Boxuan; Xiao, Yun; Lv, Qingbo; Li, Gaocan; Wang, Yunbing; Fu, Guosheng
Abstract: Atherosclerosis, as a life‐threatening cardiovascular disease with chronic inflammation and abnormal lipid enrichment, is often difficult to treat timely due to the lack of obvious symptoms. In this work, a theranostic nanoplatform is constructed for the noninvasive in vivo diagnosis, plaque‐formation inhibition, and the lesion reversal of atherosclerosis. A three‐in‐one therapeutic complex is constructed and packaged along with a polymeric photoacoustic probe into nanoparticles named as PLCDP@PMH, which indicates an atherosclerosis‐targeting accumulation and a reactive oxygen species (ROS)/matrix metalloproteinase (MMP) dual‐responsive degradation. The photoacoustic probe suggests a lesion‐specific imaging on atherosclerotic mice with an accurate and distinct recognition of plaques. At the same time, the three‐in‐one complex performs an integrated lipid management through the inhibition of macrophages M1‐polarization, liver X receptor (LXR)‐mediated up‐regulation of ATP‐binding cassette transporter A1/G1 (ABCA1/G1) and the cyclodextrin‐assisted lipid dissolution, which lead to the reduced lipid uptake, enhanced lipid efflux, and actuated lipid removal. The in vivo evaluations reveal that PLCDP@PMH can suppress the lesion progression and further reverse the formed plaques under a diet without high fat. Hence, PLCDP@PMH provides a candidate for the theranostics of early‐stage atherosclerosis and delivers an impressive potential on the reversal of formed atherosclerotic lesions. Abstract : A theranostic nanoplatform PLCDP@PMH is constructed with atherosclerosis‐targeting accumulation and reactive oxygen species (ROS)/matrix metalloproteinase (MMP) dual‐responsiveness, which indicates a plaque‐specific photoacoustic diagnosis and a three‐in‐one therapeutic strategy of integrated lipid management via reducing lipid uptake, enhancing lipid efflux, and actuating lipid removal. PLCDP@PMH provides a candidate for the diagnosis of early‐stage plaques, the inhibition of atherosclerosis progression, and the reversal of formed lesions.